Réflexions sur l’émergence d’une méthodologie de la planification prospective - Ozbekhan, Hasan (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
The recent work of a few thinkers in the United States and abroad shows with growing clarity that the idea of planning is beginning to crystallize, to have coherence and cohesiveness. This is an exciting as well as important development, especially if one remembers that the writers in question often approach the subject from quite radically differing angles of vision, from different backgrounds and from divergent intellectual commitments or personal biases. If, despite this, a convergence has become noticeable, it should be possible to think that beyond residual idiosyncracies of language and style, a planning methodology is emerging which appears capable of weaving manifold strands together into a common body of knowledge and application.For the moment, such a methodology remains open-ended. It has not yet been formalized into doctrine, and it is possible, and perhaps to be hoped, that it will remain this way. Nevertheless, its overall configuration, its main concepts and phases are now sufficiently general, so that one can describe and discuss them without reference to specific cases. My aim in these pages is to do precisely that.